2009
DOI: 10.1007/978-3-642-02279-1_9
|View full text |Cite
|
Sign up to set email alerts
|

Data Parallel Bin-Based Indexing for Answering Queries on Multi-core Architectures

Abstract: Abstract. The multi-core trend in CPUs and general purpose graphics processing units (GPUs) offers new opportunities for the database community. The increase of cores at exponential rates is likely to affect virtually every server and client in the coming decade, and presents database management systems with a huge, compelling disruption that will radically change how processing is done. This paper presents a new parallel indexing data structure for answering queries that takes full advantage of the increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Bit vectors carry the nice property of being small enough to fit in the limited gpu memory, while most bit operations nicely fall in the SIMD algorithm space. Promising results have been reported in [8]. Similar, re-engineering the algorithms to work well in a flash storage architecture have shown significant improvements [22].…”
Section: Related Workmentioning
confidence: 78%
“…Bit vectors carry the nice property of being small enough to fit in the limited gpu memory, while most bit operations nicely fall in the SIMD algorithm space. Promising results have been reported in [8]. Similar, re-engineering the algorithms to work well in a flash storage architecture have shown significant improvements [22].…”
Section: Related Workmentioning
confidence: 78%
“…• BPA -measurements reported from 20 [28]. Continuous attributes were discretized into 25 bins using Lloyd's Algorithm [29], resulting in 475 bins.…”
Section: Methodsmentioning
confidence: 99%
“…There has been an abundance of work related to using GPUs to increase the efficiency of specific database indices. For example, Gosink et al [20] created a parallel indexing data structure that uses bin-based data clusters. They showed that their GPU implementation could achieve 3× speedup over their CPU implementation.…”
Section: Related Workmentioning
confidence: 99%
“…One query-based approach, QueryDriven Visualization (QDV), is an extremely powerful strategy that couples scalable database indexing technologies, like FastBit [41], [42], [43] and DP-BIS [18], with visualization techniques to efficiently manage large-scale data, perform rapid data analysis, and support unconstrained, interactive exploration of complex data [13], [15], [16], [37].…”
Section: Introductionmentioning
confidence: 99%